2015
DOI: 10.5604/20831862.1189200
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic fitness and performance in elite female futsal players

Abstract: Despite its growing popularity, few studies have investigated specific physiological demands for elite female futsal. The aim of this study was to determine aerobic fitness in elite female futsal players using laboratory and field testing. Fourteen female futsal players from the Venezuelan National team (age =21.2±4.0 years; body mass =58.6±5.6 kg; height =161±5.0 cm) performed a progressive maximal treadmill test under laboratory conditions. Players also performed a progressive intermittent futsal-specific fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 32 publications
3
50
0
11
Order By: Relevance
“…Few reports are available regarding physiological analyses of female futsal athletes [11,41,56,57]. Here, we demonstrate that male athletes present elevated anaerobic parameters when compared with females.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Few reports are available regarding physiological analyses of female futsal athletes [11,41,56,57]. Here, we demonstrate that male athletes present elevated anaerobic parameters when compared with females.…”
Section: Discussionmentioning
confidence: 48%
“…Since both metabolisms are relevant to futsal, protocols to evaluate these parameters are ex-tremely important for training control and prescription. Although physiological evaluation of aerobic metabolism has largely improved in futsal [8][9][10][11], further efforts are required for the determination of anaerobic parameters under specific futsal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Physical demands and aerobic fitness have a link with fatigue, and as reported in our study, female futsal players showed a low aerobic fitness level (IR1 = 920±164 m). A previous investigation showed that elite level female futsal players have lower aerobic fitness (VO 2 max = 45.3±5.6 ml ∙ kg -1 ∙ min -1 ) than elite and professional female soccer players (from 49 to 58 ml ∙ kg -1 ∙ min -1 ) [ 18 ]. Coaches and sport scientists can use this new information to plan futsal training sessions, and to quantify the workload more appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Its popularity has continued to grow and so the investigation of its physiological demands and specific adaptations to its practice (Barbero-Alvarez et al, 2015). In this aspect, scientists investigated the role played by lower limb muscle power in performance and injury prevention (Croisier et al, 2008;Milioni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%